2011
DOI: 10.1007/s11095-011-0482-x
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Tryptophan Oxidation Induced by Autocatalytic Reaction of Polysorbate 20 in Protein Formulation

Abstract: A metal-binding amino acid, His31, was responsible for Trp50 oxidation of Fab induced by peroxides in PS20 present in the protein formulation. Oxidation was induced by autocatalytic degradation of PS20 and could be inhibited by antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 32 publications
0
38
1
1
Order By: Relevance
“…In particular, incubation of polysorbate 80 in air at high temperatures promotes peroxide formation, and removal of oxygen is recommended for long-term storage. The oxidation induced by peroxides as a result of polysorbate 20 degradation can be inhibited by antioxidants as shown in a study using an IgG 1 mAb Fab (Lam, Lai, Chan, Ling, & Hsu, 2011). In this study, it was shown that a Trp residue was oxidized as a result of the presence of increased levels of peroxide in polysorbate 20, and the decomposition of the polysorbate-involved free radicals.…”
Section: Surfactants and Surface-active Agentsmentioning
confidence: 60%
See 1 more Smart Citation
“…In particular, incubation of polysorbate 80 in air at high temperatures promotes peroxide formation, and removal of oxygen is recommended for long-term storage. The oxidation induced by peroxides as a result of polysorbate 20 degradation can be inhibited by antioxidants as shown in a study using an IgG 1 mAb Fab (Lam, Lai, Chan, Ling, & Hsu, 2011). In this study, it was shown that a Trp residue was oxidized as a result of the presence of increased levels of peroxide in polysorbate 20, and the decomposition of the polysorbate-involved free radicals.…”
Section: Surfactants and Surface-active Agentsmentioning
confidence: 60%
“…Reducing agents such as glutathione can reverse the oxidation by reducing the oxidized product, whereas oxygen scavengers are added molecules that more readily oxidize than the residues in a protein. The latter strategy was used successfully to inhibit oxidation of Met residues in an IgG1 mAb formulation by adding the free amino acid Met (Lam, Yang, & Cleland, 1997), and Trp oxidation in a mAb Fab fragment by adding the free amino acid Trp (Lam et al, 2011). Although the addition of Trp in the case of the mAb Fab fragment was effective, a study by Wang et al (Ji, Zhang, Cheng, & Wang, 2009) showed that the route of the Trp oxidation could govern the effectiveness of addition of Trp.…”
Section: Antioxidantsmentioning
confidence: 99%
“…95 Oxidation of Trp has only been reported in a few cases. 92,96,97 In one of those studies, oxidation of the single Trp residue in the CDR3 caused a substantial decrease in antigen binding and potency. 92 Oxidation of Trp to form various products during exposure to light or heat causes changes to the color of mAb products.…”
Section: Succinimidementioning
confidence: 99%
“…In another study, Trp was oxidized in a humanized Fab via an autocatalytic reaction of polysorbate 20 (PS20) in the formulation. PS20 is known to have peroxides depending on how the PS20 was stored (Lam et al, 2011). Formulation with PS20 containing increasing levels of peroxide resulted in a specific oxidation at Trp 50.…”
Section: Trp Oxidation In Mabsmentioning
confidence: 99%